Improving Community Knowledge in Cot Bagi on the Processing of Simplicia from Family Medicinal Plants (TOGA): Peningkatan Pengetahuan Masyarakat Cot Bagi Dalam Pengolahan Simplisia Dari Tanaman Obat Keluarga (TOGA) - Irma Zarwinda; Nurmalia Zakaria; Elfariyanti (Jurnal Mitra Pengabdian Farmasi, 2025)
Cot Bagi Village, Blang Bintang District, Aceh Besar Regency, has significant potential for the development of Family Medicinal Plants (TOGA). However, the utilization of TOGA by the community remains limited, particularly in processing harvested plants into high-quality simplicia with economic value. This community service program aimed to improve community knowledge in Cot Bagi Village regarding the processing of simplicia from TOGA. The activity was conducted through active health promotion using counseling and hands-on training, supported by educational modules. Participants’ knowledge improvement was measured using pre-test and post-test questionnaires. The results showed a substantial increase in participants’ knowledge, from 37% in the pre-test to 88.5% in the post-test, indicating a significant improvement. This program positively enhanced community understanding of proper TOGA processing, including harvesting, drying, storage, and simplicia preparation. The activity is expected to encourage optimal utilization of TOGA and support community independence and welfare.